Auditor of personality and performance throughout the period of the pandemic - Budiandru Budiandru (Accounting Department, Faculty of Business and Economics, Universitas Islam Indonesia, 2022)
Existing audit standards must guide auditors in carrying out their profession. Audit standards regulate auditors in compiling reports with good performance and according to the professional code of ethics. The goal of this study was to examine the impact of professional ethics, auditor independence, auditor experience, and auditor professionalism on auditor performance during a pandemic by taking samples from public accounting firms in Jakarta and Surabaya with 170 respondents. Using the Structural Equation Model (SEM), this study aims to solve the research questions. The findings of the study showed that auditor professionalism had an effect on auditor performance, while professional ethics, independence, and experience of auditors had no such effect. Public accounting firms must improve and maintain the professionalism of each auditor in order to avoid the manipulation of financial statements and produce maximum performance.